Switch-on NIR probe for specific detection of Hg2+ ion in aqueous medium and in mitochondria - Agarwalla, Hrideshg; Mahajan, Pankaj S.; Sahu, Debashis; Taye, Nandaraj; Ganguly, Bishwajit; Mhaske, Santosh B.; Chattopadhyay, Samit; Das, Amitava (Inorganic Chemistry, 2016)
A new 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene (BODIPY)-based probe molecule (L) is synthesized for specific binding to Hg2+ ion in physiological condition with an associated luminescence ON response in the near-IR region of the spectrum. Appropriate functionalization in the 5-position of each of two pyrrole moieties with styryl functionality in a BODIPY core helped us in achieving the extended conjugation and a facile intramolecular charge transfer transition with a narrow energy gap for frontier orbitals. This accounted for a poor emission quantum yield for the probe molecule L. Binding to. Hg2+ helped in interrupting the facile intramolecular charge transfer (ICT) process that was initially operational for L. This resulted in a hypsochromic shift of absorption band and a turn-on luminescence response with lambda(Em)(max) of 650 nm on specific binding to Hg2+. Observed spectral changes are rationalized based on quantum chemical calculations. Interestingly, this reagent is found to be localized preferentially in the mitochondria of the live human colon cancer (Hct116) cells. Mitochondria is one of the major targets for localization of He2+, which actually decreases the mitochondrial membrane potential and modifies various proteins having sulfudryl functionality(ies) to cause cell apoptosis. Considering these, ability of the present reagent to specifically recognize Hg2+] in the mitochondrial region of the live Hct116 cells has significance.

Synthesis and biological evaluation of new fluconazole β-lactam conjugates linked via 1,2,3-triazole - Divse, Jaisingh M.; Mhaske, Santosh B.; Charolkar, Chaitanya R.; Sant, Duhita G.; Tupe, Santosh G.; Deshpande, Mukund V.; Khedkar, Vijay M.; Nawale, Laxman U.; Sarkar, Dhiman; Pore, Vandana S. (New Journal of Chemistry, 2017)
Novel 1,2,3-triazole-linked β-lactam–fluconazole conjugates 12(a–l) were designed and synthesized. The compounds showed potent antifungal activity against two pathogenic Candida strains; Candida albicans ATCC 24433 and Candida albicans ATCC 10231 with MIC values in the range of 0.0625–2 μg mL−1. Compounds 12h, 12j and 12k showed promising antifungal activity against all the tested fungal pathogens except C. neoformans ATCC 34554 compared to fluconazole. Compound 12j in which the β-lactam ring was formed using para-anisidine and benzaldehyde was found to be more potent than fluconazole against all the fungal strains with an IC50 value of <0.015 μg mL−1 for Candida albicans (ATCC 24433). Mechanistic studies for active compounds revealed that the antifungal action was due to ergosterol inhibition. Compounds 12h and 12j at a concentration of 0.125 μg mL−1 caused 91.5 and 96.8% ergosterol depletion, respectively, compared to fluconazole which at the same concentration caused 49% ergosterol depletion. The molecular docking study revealed that all the fluconazole β-lactam conjugates 12(a–l) could snugly fit into the active site of lanosterol 14α-demethylase (CYP51) with varying degrees of affinities. As anticipated, the binding energy for compound 12j (−58.961 kcal mol−1) was much smaller than that for fluconazole (−52.92 kcal mol−1). The synthesized compounds have therapeutic potential for the control of candidemia.

Synthesis of methyl-protected (+/-)-chlorizidine A - Mahajan, Jyoti P.; Mhaske, Santosh B. (Organic Letters, 2017)
The first total synthesis of the methyl-protected (+/-)-chlorizidine A has been achieved in 10 steps. Pd-catalyzed decarboxylative coupling and late-stage oxidation were utilized to, construct the 5H-pyrrolo[2,1-a]isoindol-5-one scaffold. Samarium(II) iodide mediated Reformatsky reaction and intramolecular Mitsunobu reactions were efficiently applied for the synthesis of the 2,3-dihydropyrrolizine ring system. Chlorizidine A is highly prone to degradation; hence, methyl-protected (+/-)-chlorizidine A was prepared.

Synthesis of o-methyl trifluoromethyl sulfide substituted benzophenones via 1,2-difunctionalization of aryne by insertion into the C-C bond - Ahire, Milind M.; Khan, Ruhima; Mhaske, Santosh B. (Organic Letters, 2017)
An efficient process for the preparation of valuable o-methyl trifluoromethyi sulfide substituted benzopheriones has been developed. The transition-metal-free method features insertion of aryne into a C-C sigma-bond under mild reaction conditions for the first time to achieve ortho-difunctionalized arenes containing a pharmaceutically important trifluoromethylthio functional group. A wide substrate, scope has been demonstrated for the developed protocol.

Synthesis of succinimide derivatives by NHC-catalyzed stetter reaction of aromatic aldehydes with N-substituted itaconimides - Ahire, Milind M.; Mhaske, Santosh B. (ACS Omega, 2017)
An N-heterocyclic carbene-catalyzed intermolecular Stetter reaction of aromatic aldehydes with N-substituted itaconimides has been developed. A delicate balance between the Stetter reaction and the competing isomerization of the itaconimide double bond has been achieved in this operationally simple reaction to afford valuable new succinimide derivatives containing 1,4 and 1,5 dicarbonyl scaffolds in good to excellent yields. The reaction tolerates variable substituents on both aldehydes and N-substituted itaconimides.

Silver-mediated oxidative decarboxylative intramolecular asymmetric radical cyclization (C sp3 –C sp2 ) via memory of chirality: access to circumdatin alkaloids - Mahajan, Pankaj S.; Mhaske, Santosh B. (Organic Letters, 2018)
A novel silver-mediated oxidative decarboxylative intramolecular asymmetric radical cyclization has been developed to form a Csp3–Csp2 bond via memory of chirality. The application of the process has been demonstrated for the synthesis of the circumdatin class of alkaloids in high enantiopurity with retention of the configuration. The developed protocol is mild and works with an inexpensive silver catalyst in the absence of ligand, base, or additives. The involvement of a monoradical in the reaction has been established by trapping the radical intermediate.

Stereoselective construction of deoxy-cruciferane alkaloids by NHC-catalyzed intramolecular annulation of homoenolate with quinazolinone - Ahire, Milind M.; Pol, Mahesh D.; Kavale, Dattatry S; Gonnade, Rajesh G.; Mhaske, Santosh B. (Organic & Biomolecular Chemistry, 2019)
Chiral N-heterocyclic carbene (NHC)-catalyzed intramolecular [3 + 2] annulation of enals with an unactivated imine moiety of quinazolinone via formal homoenolate cycloaddition has been demonstrated. It is an excellent approach for stereoselective syntheses of deoxy-cruciferane alkaloids comprising a biologically important pyrroloindoline scaffold. Notably, this is the first report on the NHC-catalyzed asymmetric intramolecular homoenolate annulation with cyclic N-acyl amidine.